Circular dichroism of quantum defects in carbon nanotubes created by photocatalytic oxygen functionalization [data] - Sebastian, Finn; Kaminski, Leon; Bendel, Christoph; Yomogida, Yohei; Hosokawa, Yuuya; Li, Han; Lindenthal, Sebastian; Flavel, Benjamin S.; Yanagi, Kazuhiro; Zaumseil, Jana (Universität, 2025)
This repository contains the data of the publication "Circular dichroism of quantum defects in carbon nanotubes created by photocatalytic oxygen functionalization" (Nat. Commun. 2025, 16, 5107, doi: 10.1038/s41467-025-60342-y)